TYPE 1 VERSUS TYPE 3 NEOVASCULARIZATION IN PIGMENT EPITHELIAL DETACHMENTS ASSOCIATED WITH AGE-RELATED MACULAR DEGENERATION AFTER ANTI-VASCULAR ENDOTHELIAL GROWTH FACTOR THERAPY: A Prospective Study. (December 2016) - Chen, Xuejing; Al-Sheikh, Mayss; Chan, Clement K.; Hariri, Amir H.; Abraham, Prema; Lalezary, Maziar; Lin, Steven G.; Sadda, SriniVas; Sarraf, David
Abstract : Purpose: To evaluate the response to aflibercept therapy for Type 1 and Type 3 neovascularization in pigment epithelial detachments associated with treatment-naive, neovascular age-related macular degeneration. Methods: In this multicentered, prospective study, eligible eyes underwent an intravitreal aflibercept injection protocol for 12 months. Visual acuity and morphologic features of the pigment epithelial detachments were compared at baseline and follow-up intervals between eyes with Type 1 versus Type 3 neovascularization. Results: Thirty-six eyes were analyzed. At 12 months, Type 1 lesions showed a 4.5 ± 23 Early Treatment of Diabetic Retinopathy Study letter improvement ( P = 0.1665) versus a 14 ± 11 ( P = 0.0072) letter improvement with Type 3 lesions. Both Type 1 and 3 eyes showed a significant decrease in pigment epithelial detachment size, subretinal fluid, and subretinal hyperreflective material; however, Type 3 eyes had a greater reduction in pigment epithelial detachment size and subretinal hyperreflective material, as well as a reduction in central retinal thickness. Type 1 eyes required an average of 1.636 (range, 1–4) injections to resolve fluid, which was greater than Type 3 eyes, which required an average of 1.143 (range, 1–2) injections ( P = 0.0251). Conclusion: Intravitreal aflibercept injections were efficacious for pigment epithelial detachments, but baseline and follow-up anatomical and functional outcomes differed in Type 1 versus Type 3 neovascularization. The better response of Type 3 eyes with fewer injections suggests that differentiation of the neovascularization subtype at the initial diagnosis may allow for a more tailored, optimal therapy. Abstract : A 1-year multicentered, prospective study of aflibercept therapy for Type 1 and Type 3 neovascularization in pigment epithelial detachments associated with treatment-naive, neovascular age-related macular degeneration was performed. Aflibercept monotherapy was efficacious for pigment epithelial detachments, but baseline and follow-up anatomical and functional outcomes differed between Type 1 and Type 3 neovascularization.